Squash and Tissue print protocols for quick detection of Tomato leaf curl New Delhi virus-potato in fresh and ethanol preserved single whitefly - Sridhar, Jandrajupalli; Venkateswarlu, Vallepu; Jeevalatha, Arjunan; Malik, kamlesh; Bhatnagar, Anuj; Singh, Bir Pal (Potato Journal, 2016)
Squash and tissue-print PCR protocols were designed to detect Tomato leaf curl New Delhi virus-potato in Bemisia tabaci and Trialeurodes vaporariorum in uniplex, and simultaneously along with internal control. Both whiteflies species were given an acquisition feeding of 24 hours separately on pure culture of this virus. Then, the individual whitefly tissues were directly printed on nitrocellulose membrane (tissue print), and whiteflies were crushed in PBST buffer and spotted on membrane in squash print method. The uniplex PCR assay of eluted DNA revealed a sharp amplicon of 491 bp region of coat protein gene of ToLCNDV-potato. In simultaneous detection, a sharp amplicon of 161, 300 and 491 bp for T. vaporariorum, B. tabaci and ToLCNDV-potato respectively were observed in a single reaction. Gene sequencing results showed 99-100% similarity with reported sequences of ToLCNDV-potato. The protocols were validated for their sensitivity and reproducibility using ethanol preserved single whitefly collected from potato fields of Punjab, Uttar Pradesh, Madhya Pradesh and Maharashtra and concurrent results were observed on repetition. This is the first report to detect ToLCNDV-potato in single whitefly along with internal control which will not only strengthen the virus diagnostics but also help to screen the field collected whiteflies for their viruliferous nature and to understand the epidemiology of virus virus vectors aid in taking timely vector management decisions.